PENINGKATAN LITERASI MANAJEMEN KEUANGAN DAN PEMASARAN DIGITAL BAGI PELAKU USAHA PARIWISATA DAN UMKM - Ujang Eri Jaenudin; Rizky Ridwan; Dheri Febiyani Lestari; Alfin Nur Arifah; Aditia Abdurachman; Taupik Akbar (Universitas Kadiri, 2024)
This program aims to improve financial literacy and digital financial management for tourism entrepreneurs and MSMEs in Darmacaang Village, Ciamis, West Java. Low financial literacy and reliance on traditional management methods are major obstacles to the growth of local tourism businesses. The program uses a participatory approach, starting with socialization and surveys to identify the needs of tourism entrepreneurs and MSMEs, followed by in-person and online training on financial literacy, digital financial management, and digital marketing, particularly in the tourism sector. Participants receive regular mentoring to ensure the application of the knowledge gained. The results show a significant increase in participants' understanding of digital financial management, adoption of e-wallet applications, and use of digital marketing platforms to expand tourism markets. Participants also demonstrated increased confidence in managing tourism businesses amid economic challenges, contributing to the sustainability and growth of local MSMEs and tourism, and supporting regional economic development